Leiblicher Logos : 14 Künstlerinnen aus Deutschland. - Staatsgalerie Stuttgart; Beuys, Joseph; Block, René; Diacono, Mario; Duchamp, Marcel; Gröting, Asta; Haerdter, Michael; Haist, Erna; Inboden, Gudrun; Kafka, Franz; Karrenberg, Katharina; Kersting, Hannelore; et al. (Stuttgart : Institut für Auslandsbeziehungen, 1995)
Demming, Dagmar ; Denda, Elke ; Eichhorn, Maria ; Fritsch, Katharina ; Genzken, Isa ; Gröting, Asta ; Horn, Rebecca ; Karrenberg, Katharina ; Sander, Karin ; Siem, Wiebke ; Stadtbäumer, Pia ; Trockel, Rosemarie ; Weiss-Leder, Ute ; Yufen Qin
biografie
Leiblicher Logos : 14 Künstlerinnen aus Deutschland, Staatsgalerie, Stuttgart, 18.02. - 09.04.1995
German
boek